2014
DOI: 10.1128/genomea.00413-14
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Erwinia amylovora Bacteriophage vB_EamM_Ea35-70

Abstract: The complete genome of an Erwinia amylovora bacteriophage, vB_EamM_Ea35-70 (Ea35-70), is 271,084 bp, encodes 318 putative proteins, and contains one tRNA. Comparative analysis with other Myoviridae genomes suggests that Ea35-70 is related to the Phikzlikevirus genus within the family Myoviridae, since 26% of Ea35-70 proteins share homology to proteins in Pseudomonas phage φKZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…Further searches showed that the 10 proteins encoded by these genes in SPN3US also have homologs in other recently identified ϕKZ-related phages, such as Vibrio phage JM2012 (25) and Erwinia phage Ea35-70 (46), and other giant phages (Table 6), supporting the broader relevance of utilizing a genetic system to study SPN3US. Examples of several proteins well conserved in all myoviruses (major head, sheath, and terminase proteins [47]) are also included in Table 6 to illustrate the intrinsically divergent nature of homologous proteins in these phages.…”
Section: Discussionmentioning
confidence: 52%
“…Further searches showed that the 10 proteins encoded by these genes in SPN3US also have homologs in other recently identified ϕKZ-related phages, such as Vibrio phage JM2012 (25) and Erwinia phage Ea35-70 (46), and other giant phages (Table 6), supporting the broader relevance of utilizing a genetic system to study SPN3US. Examples of several proteins well conserved in all myoviruses (major head, sheath, and terminase proteins [47]) are also included in Table 6 to illustrate the intrinsically divergent nature of homologous proteins in these phages.…”
Section: Discussionmentioning
confidence: 52%
“…The four jumbo myovirus groups package DNA by headful packaging based on homology of their putative terminase genes to the phiKZ terminase ( 9 ). Three of these genomically permuted myovirus groups were assigned their base pair (bp) 1 by alignment to previously published genomes by use of BLASTN ( 10 ) and Gepard ( 11 ) (Ea35-70 for the Deimos-Minion group [ 12 ], EL [ 13 , 14 ] for the RisingSun group, and SPN3US [ 15 ] for the Caitlin group). vB_EamM_Yoloswag shared very little DNA homology with any other phage; therefore, its bp 1 was assigned to position its putative terminase at the beginning of the genome.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Consequently, more than thirty phages related to ϕKZ infecting a range of hosts including Salmonella (e.g., SPN3US), Erwinia amylovora (e.g., Ea35-70), Cronobacter sakazakii (e.g., CR5) and Vibrio spp. (e.g., JM-2012) have now been isolated with the goal of developing novel phage-based therapeutics (Lee et al, 2011 , 2016 ; Jang et al, 2013 ; Meczker et al, 2014 ; Yagubi et al, 2014 ; Bhunchoth et al, 2016 ; Danis-Wlodarczyk et al, 2016 ). For example, PhiEaH2 is one of two phages in “Erwiphage,” the first marketed bacteriophage-based pesticide against E. amylovora in Hungary (Meczker et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%